'Stuck' in nonstandard schedules? Married couples' nonstandard work schedules over the life course. Issue 1 (1st January 2021) - Leupp, Katrina; Kornrich, Sabino; Brines, Julie
ABSTRACT: Though employment outside of regular daytime business hours has remained high since the 1990s, trends in nonstandard employment schedules over the life course and across households remain under-examined. The consequences of nonstandard scheduling extend to workers, their spouse, and children, urging greater attention to the distribution of nonstandard schedules at the couple-level. Using all three waves of the National Survey of Families and Households, this article examines the prevalence, persistence and sociodemographic patterns of rotating and night employment at the couple-level, following 913 married couples in the United States as they aged from the late 1980s to early 2000s. Though aging reduced the likelihood that couples had one or both spouses working nonstandard hours, roughly one-third of couples with nonstandard scheduling continued to experience nonstandard schedules during the subsequent observation period. Nonstandard schedules were stratified by education and race/ethnicity. This stratification persisted as couples aged, even after controlling for prior work schedules. Findings suggest that disadvantaged couples remain disproportionately exposed to schedules associated with negative outcomes for family well-being across the life course.